THE OCCURRENCE OF NUTRITIONAL AND MANAGEMENT-RELATED DISEASES IN DAIRY SMALLHOLDING FARMS IN INDONESIA - E. Kusumanti, dan Widiyanto (AGROMEDIA: Berkala Ilmiah Ilmu-ilmu Pertanian, 2016)
ABSTRACT            The aim of the study was to reveal the major facets of animal health status as related to nutrition and farming management upon milk production in smallholding dairy farms. A cross-sectional study was conducted in Boyolali region, Indonesia, involving 50 randomly selected farms consisted of 200 lactating Frisiens Holstein-crossbreed cows. Data  related to milk yield, feedstuff composition and clinical evaluation were analyzed with T-test using SPSS for Windows whilst socio-demographic aspect obtained from personal interview were analyzed descriptively based on Chi-square. The result showed that net energy for lactation (NEL) of feedstuff could  provide 13 l/day in which mixed roughages and agricultural by-products tend to be preferable when compared with other feedstuffs combination (P=0.052). There was imbalance of Ca:P ratio (1:2)which could induce low milk production. Low quality of feedstuff provoked negative energy balance which caused metabolic disturbances. It showed that prevalence for clinical mastitis was 10.85% and nutritional diseases was 34.8% at which bloat was the most lethally disease. Administration of natrium chloride (NaCl) 0.91-3.17% DM/day whithout compesated by sufficient water consumption affected (P0.05) mastitis ocurrence. Skin diseases were detected in 85.92% of  selected cows, while 13% of cows were under helminthiasis treatment. In conclusion, over administration of NaCl and imbalance of Ca and P ratio led to the low level of milk production and disease occurence in the smallholders lactating cows. From this, appropriate method and devices to elevate milk production with respect to zootechnique skill of the farmer is necessary through the intervention of government. Keywords: smallholder farms, milk production, agricultural-by-products, feeding regime, diseases